The Impact of Green Innovation on Employment Growth in Europe - Georg Licht; Bettina Peters (WWWforEurope, 2013)
This paper studies the impact of environmental innovation on employment growth using firmlevel data for 16 European countries and the period 2006-2008. It extends the model by Harrison et al (2008) in order to distinguish between employment effects of environmental and non-environmental product as well as process innovation. By looking at country and sector level differences, it also generates new insights into the heterogeneity of the environmental innovation-employment growth link along different dimensions. The results demonstrate that both environmental and non-environmental product innovations are conducive to employment growth in European firms. We estimate a gross employment effect of product innovation for both types of product innovators that is very similar in nearly all countries and sectors. That is, in most cases a one-percent increase in the sales due to new products for environmental product innovators also increases gross employment by one percent. This implies that there is no evidence that environmentally-friendly new products are produced with higher or lower efficiency than old products. Yet, we observe differences in the contribution of environmental and non-environmental product innovation to employment growth across countries or sectors that are the result of differences in the average innovation engagement and innovation success across countries or sectors. The absolute contribution to employment growth is positive for both types of new products. However, we find mixed evidence for the relative importance. In manufacturing the contribution of environmental product innovators was larger than that of non-environmental product innovators in half of the countries. In services, however, non-environmental product innovators matters more for growth in the vast majority of countries. In contrast, environmental and non-environmental process innovation plays only a little role for employment growth.
Keywords: O33; J23; L80; C21; C23; 330; Environmental innovation; employment growth; Europe